2020
DOI: 10.3758/s13428-020-01465-6
|View full text |Cite
|
Sign up to set email alerts
|

The application of noninvasive, restraint-free eye-tracking methods for use with nonhuman primates

Abstract: Over the past 50 years there has been a strong interest in applying eye-tracking techniques to study a myriad of questions related to human and nonhuman primate psychological processes. Eye movements and fixations can provide qualitative and quantitative insights into cognitive processes of nonverbal populations such as nonhuman primates, clarifying the evolutionary, physiological, and representational underpinnings of human cognition. While early attempts at nonhuman primate eye tracking were relatively crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 173 publications
1
51
0
Order By: Relevance
“…However, the arrival of eye tracker techniques, which allowed for following the gaze of subjects with a minimal margin error, allowed to incorporate new ways to explore the existence of theory of mind in apes with a simple experimental design based on the anticipatory look on others’ movement [ 59 , 60 ]. Plus, the method is non-invasive and restraint-free [ 61 ]. Another milestone of technology in our discipline has been the use of drones in marine studies, because “behavioural observations are typically limited to records of animal surfacings obtained from a horizontal perspective” but “drones UAS provided three times more observational capacity than boat-based observations alone (300 vs. 103 min); provided more and longer observations plus enable documentation of multiple novel gray whale foraging tactics and social events not identified from boat-based observation” ([ 62 ], p. 359).…”
Section: Resultsmentioning
confidence: 99%
“…However, the arrival of eye tracker techniques, which allowed for following the gaze of subjects with a minimal margin error, allowed to incorporate new ways to explore the existence of theory of mind in apes with a simple experimental design based on the anticipatory look on others’ movement [ 59 , 60 ]. Plus, the method is non-invasive and restraint-free [ 61 ]. Another milestone of technology in our discipline has been the use of drones in marine studies, because “behavioural observations are typically limited to records of animal surfacings obtained from a horizontal perspective” but “drones UAS provided three times more observational capacity than boat-based observations alone (300 vs. 103 min); provided more and longer observations plus enable documentation of multiple novel gray whale foraging tactics and social events not identified from boat-based observation” ([ 62 ], p. 359).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of effect of female colouration on male sexual behaviours -or in other words, the lack of male choice for darker/redder females-is surprising given that previous studies suggested a potential role of female colouration on male mate choice in Japanese macaques over-estimated due to the binary choice, the lack of familiarity with the stimuli which significantly matters in communication (e.g., visual trait: Higham et al, 2011;odorant trait: Setchell et al, 2010;auditory trait: Townsend et al, 2011), or the lack of precise measure of attention such as tracking fine-scale eye movements (Hopper et al, 2020;Yorzinski et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…An additional avenue of research that now shows promise for a number of species, such as primates (Hopper et al, 2020) and dogs (Somppi et al, 2012), is the use of eye tracking. Eye tracking can be conducted non-invasively and thus is of increasing application to a wider scope of research setups such as in zoos (Hopper et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An additional avenue of research that now shows promise for a number of species, such as primates (Hopper et al, 2020) and dogs (Somppi et al, 2012), is the use of eye tracking. Eye tracking can be conducted non-invasively and thus is of increasing application to a wider scope of research setups such as in zoos (Hopper et al, 2020). The benefit of this approach is that it allows one to examine in detail gaze responses to social stimuli, such as how species explore facial images (Kano et al, 2012;Wilson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%